Challenges in the implementation of patient identification and the Gender Identity Law in healthcare institutions in Buenos Aires - Perez, Silvia Gabriela (2024)
Introduction: Patient identification is a key component of Patient Safety goals. In the context of gender identity (GI) regulations, the adaptation of identification protocols is required for compliant implementation. The objective was to identify challenges and tensions in patient identification as a safety goal and its intersection with the current gender identity legislation in Argentina.Methods: A qualitative approach was used to collect data from seven healthcare institutions with patient admissions, selected based on their different profiles in terms of sector (public/private), patient safety accreditation process, and type of care (specialized/general). Grounded theory was employed to identify common institutional patterns.Results: Three institutional situations were identified: 1. Contradiction: where compliance with GI regulations is perceived to undermine secure patient identification; 2. Potential convergence: although GI regulations are not fully implemented in patient identification, institutions deploy informal strategies to comply with them; 3. Convergence: institutions that have made changes to records and systems in line with GI. All institutions acknowledge the need for training in the care of transgender, transvestite, and non-binary patients.Conclusions: Strengthening institutional policies based on safety goals and adherence to gender identity legislation is necessary. Organizational changes are essential, and training is needed to address the care of transgender, transvestite, and non-binary patients effectively.